2019
DOI: 10.1017/s1474747218000410
|View full text |Cite
|
Sign up to set email alerts
|

Navigating complex financial decisions at retirement: evidence from annuity choices in public sector pensions

Abstract: Choices regarding the disposition of wealth at retirement can have substantial implications for retirement income security. We analyze the factors determining annuity payout option choices within the context of a public sector defined pension plan with no default annuity option. Using combined administrative records and survey data, we explore the role of individual and household characteristics as well as risk preferences, time preferences, and financial literacy. We also document retiree well-being and satis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…The analyses illuminate a variety of paths and labor supply options for individuals as they shift from FCJs into retirement, with the specific choice of paths driven by Social Security and pension characteristics, interest rates and returns to retirement saving, employer return-to-work provisions, and the availability of retiree health plans. Clark et al (2019) show that only 37% of retirees surveyed three or more years post-retirement thought they had saved enough. Accordingly, as Bronshtein et al (2019) argue, it may be critical for people to work longer, so as to enhance their retirement security.…”
Section: Discussionmentioning
confidence: 98%
“…The analyses illuminate a variety of paths and labor supply options for individuals as they shift from FCJs into retirement, with the specific choice of paths driven by Social Security and pension characteristics, interest rates and returns to retirement saving, employer return-to-work provisions, and the availability of retiree health plans. Clark et al (2019) show that only 37% of retirees surveyed three or more years post-retirement thought they had saved enough. Accordingly, as Bronshtein et al (2019) argue, it may be critical for people to work longer, so as to enhance their retirement security.…”
Section: Discussionmentioning
confidence: 98%
“…As such, we might expect some different patterns of annuity choices by retirees from state and local retirement plans. Clark et al (2019) found that among retirees in North Carolina, men are much more likely to choose a J&S annuity compared to women (61% compared to only 35%). 17 The difference in the proportion of women selecting J&S probably reflects the fact that Panel A. J&S 100% option benefit, assuming $1,000 monthly single life benefit; 8% interest; public safety worker mortality; amount in parenthesis is the change from These calculations use mortality tables for the specified retiree group and contingent survivors from the headcount-weighted rates in the exposure draft of the Pub-2010 Public Retirement Plans Mortality Tables released by the Society of Actuaries (https://www.soa.org/ experience-studies/2018/pub-2010-retirement-plans/), projected generationally using Scale MP-2017 assuming a retirement date in 2018.…”
Section: Does the Price Of Jands Annuity Matter?mentioning
confidence: 99%
“…The hypothetical retiree considered in Table 7 is 60 years old with a 61-year-old beneficiary. 19 For full details on calculations such as those in Table 7, see Clark et al (2019).…”
Section: Change In the Likelihood Of Choosing A Jands Annuity Due To A mentioning
confidence: 99%
See 2 more Smart Citations